2018
DOI: 10.1186/s12974-018-1252-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal influenza vaccination rescues impairments of social behavior and lamination in a mouse model of autism

Abstract: BackgroundPrenatal infection is a substantial risk factor for neurodevelopmental disorders such as autism in offspring. We have previously reported that influenza vaccination (VAC) during early pregnancy contributes to neurogenesis and behavioral function in offspring.ResultsHere, we probe the efficacy of VAC pretreatment on autism-like behaviors in a lipopolysaccharide (LPS)-induced maternal immune activation (MIA) mouse model. We show that VAC improves abnormal fetal brain cytoarchitecture and lamination, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…Specifically, we exposed pregnant mice to poly(I:C), a synthetic mimetic of viral dsRNA analog, a well-documented mouse model of MIA. We and others have reported that poly(I:C)-induced MIA precipitates altered brain and behavioral phenotypes in offspring that mirror abnormalities observed in ASD and related neurodevelopmental conditions such as schizophrenia (Meyer et al, 2006 ; Li et al, 2015 ; Wei et al, 2016 ; Wu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 77%
“…Specifically, we exposed pregnant mice to poly(I:C), a synthetic mimetic of viral dsRNA analog, a well-documented mouse model of MIA. We and others have reported that poly(I:C)-induced MIA precipitates altered brain and behavioral phenotypes in offspring that mirror abnormalities observed in ASD and related neurodevelopmental conditions such as schizophrenia (Meyer et al, 2006 ; Li et al, 2015 ; Wei et al, 2016 ; Wu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 77%
“…Therefore, MIA models for schizophrenia frequently induce an activation of the maternal immune response by prenatal injections with immunostimulants like polyinosinic–polycytidylic acid (Poly I:C) or lipopolysaccharide (LPS). The most common cognitive and behavioral abnormalities in these models were observed for parameters like prepulse inhibition [ 191 , 192 , 193 , 194 , 195 , 196 , 197 ], latent inhibition [ 195 , 198 ] and social interaction [ 193 , 199 , 200 ]. In rhesus monkeys, a Poly I:C-induced maternal immune challenge increased repetitive behavior patterns and reduced communication, as well as social interactions in the offspring [ 201 ].…”
Section: Structural and Functional Hippocampus Deviations In Animal M...mentioning
confidence: 99%
“…Thus, their contribution to both the acute and long-term effects of prenatal immune insult might be particularly important. Indeed, many MIA protocols resulted in changes in microglial density and activation states in offspring in various brain regions that were observed already in the embryonic stage (Wu et al, 2018), shortly after birth (Li et al, 2014), and in adulthood (Hadar et al, 2017;Van den Eynde et al, 2014;Zhu et al, 2014). However, in other studies, these differences were not detected (Corradini et al, 2018;Garay et al, 2013;Giovanoli et al, 2015Giovanoli et al, , 2016.…”
Section: Microgliamentioning
confidence: 90%